Temperature and Pressure Effects on HMX/Graphene via ReaxFF Molecular Dynamics Simulations - Yun, Xiaopeng; Zhang, Li (Frontiers in Mechanical Engineering, 2022)
Studying the thermal decomposition of energetic materials at high temperatures can provide detailed reaction and mechanistic information, which is critical for understanding the reactivity of energetic materials, designing mixed explosives, and achieving improved safety. In this work, the effects of temperature and pressure on graphene (Gr)-based HMX crystals were investigated using ReaxFF molecular dynamics simulations. The thermal decomposition processes of perfect HMX crystals, HMX crystals with (001), (010), or (100) crystal planes, and HMX/Gr mixed systems were studied at high temperatures and pressures. In the mixed systems, different configurations of HMX molecules adsorbed on the Gr surface were confirmed by theoretical calculation methods. In the pressure range from atmospheric pressure to 31 GPa, 3, 5, and 3 configurations of HMX adsorbed on the Gr surface were identified for the (001)/Gr, (010)/Gr, and (100)/Gr systems, respectively. The time-dependent curves for the evolution of fragments, intermediates, and pyrolysis products were analyzed. The rate constant for the thermal decomposition of HMX was found to be significantly affected by the addition of Gr. In particular, the thermal decomposition reaction was strongly inhibited in the (010)/Gr system. This result indicates that Gr promotes an anisotropic thermal effect resulting from the steric hindrance of the NO2 functional groups and the interaction between Gr and HMX molecules. Gr also affected the initial reaction pathway of homolytic N–NO2 bond cleavage, with C=O, C–OH, and C–OC bonds on the Gr surface participating in the formation of nitro radicals and HONO.